A Brief Overview of Social Engineering: Muhammad Shairoze Malik - Malik, Muhammad Shairoze Malik (International Journal for Electronic Crime Investigation, 2020)
Abstract:Right now digitization, the requirement for information protection and information security is verysignificant. The IT organizations today lean toward their information over everything. Not just fororganizations, information security is significant for any person. Be that as it may, regardless of howsecure is the organization, how best in class is the technology utilized or what amount cutting-edge theirproduct is, there's as yet a weakness in each segment known as 'Human'. The craft of acquiring sensitivedata from a person is known as Social Engineering. Technology has advanced rapidly in recent years, butthe danger of Social Engineering still persists in the society. This is mostly due to lack of awarenessregarding social engineering attack patterns. Social engineering is an extremely basic practice toaccumulate data and touchy information using portable numbers, messages, SMS or directmethodology. Social engineering can be extremely valuable for the aggressor whenever done in anappropriate way. This paper will look into some of the basic and rudimentary techniques used byattackers to gain personal information about victims. The goal of the article is to enable others insuccessfully defending against social engineering attacks by having the knowledge into how theseattacks are performed.